Vitamin D Deficiency and Its Clinical Correlates in Children with Dermo-Respiratory Syndrome: A Prospective Study (Herald of the National Children's Medical Center, 2025)
Aim. Dermo-respiratory syndrome (DRS) in children is a multifactorial condition frequently associ- ated with allergic manifestations and recurrent respiratory diseases. Vitamin D deficiency has been proposed as a contributing factor to immune dysregulation in this patient population, yet its role remains insufficiently defined in the pediatric setting.Materials and methods. This prospective study included 151 children aged 3–15 years diagnosed with DRS and 50 age-matched healthy controls. Anthropometric measurements, body mass index (BMI), serum 25(OH)D levels, and relevant biochemical and hematological markers were evaluated. Subgroups were analyzed based on vitamin D status, severity of clinical manifestations, and frequency of exacerbations. Statistical analysis included ANOVA and X² tests to assess differences between groups.Results. Vitamin D deficiency (
Keywords: dermo-respiratory syndrome; vitamin D deficiency; children; BMI; exacerbations; pediatrics